2016
DOI: 10.1007/s12250-016-3734-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of multi-epitope-based vaccine candidates administered with the adjuvant Gp96 against rabies

Abstract: Rabies, a zoonotic disease, causes > 55,000 human deaths globally and results in at least 500 million dollars in losses every year. The currently available rabies vaccines are mainly inactivated and attenuated vaccines, which have been linked with clinical diseases in animals. Thus, a rabies vaccine with high safety and efficacy is urgently needed. Peptide vaccines are known for their low cost, simple production procedures and high safety. Therefore, in this study, we examined the efficacy of multi-epitope-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…It is necessary to formulate novel strategies to develop non-toxic adjuvants and less immunogenic vaccine delivery carriers to prevent various animal diseases. Several host-, pathogen-, and non-pathogenderived Hsp90 were exploited as adjuvants with promising results (Echeverría et al, 2006;Mohit et al, 2011;Wang S. et al, 2011;Ju et al, 2014;Albarracín et al, 2015;Niu et al, 2016;Zhu et al, 2016;Bengoa Luoni et al, 2019;Sánchez López et al, 2019). This review presents a comprehensive revision of the adjuvant properties of Hsp90s and their potential application in the adjuvant design of vaccines to prevent infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to formulate novel strategies to develop non-toxic adjuvants and less immunogenic vaccine delivery carriers to prevent various animal diseases. Several host-, pathogen-, and non-pathogenderived Hsp90 were exploited as adjuvants with promising results (Echeverría et al, 2006;Mohit et al, 2011;Wang S. et al, 2011;Ju et al, 2014;Albarracín et al, 2015;Niu et al, 2016;Zhu et al, 2016;Bengoa Luoni et al, 2019;Sánchez López et al, 2019). This review presents a comprehensive revision of the adjuvant properties of Hsp90s and their potential application in the adjuvant design of vaccines to prevent infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, SAG1 immunization was always analyzed with an adjuvant to generate a strong Th1 immune response (Wang and Yin, 2014). Previous studies evaluating the adjuvant capacity of the murine heat shock protein Gp96 fused to antigenic peptides from different pathogenic viruses showed that Gp96 significantly increases the specific IgG2a/b response against the carried peptides (Chen et al, 2013;Ju et al, 2014;Niu et al, 2016). In addition, some authors showed that while a high immune response occurs against the fused antigen of interest, they did not observe an immune response against Gp96 or HSP90.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of novel rabies vaccines based mainly on the viral glycoprotein have been tested in animals using mainly PEP regimens. Many of them such as a yeast-derived protein vaccine [28] or peptide vaccines showed lack of complete efficacy and are thus unlikely to progress to clinical trials [29,30]. Others, such as genetically engineered live attenuated rabies viruses, which were shown in animals to be safe and efficacious [31,32] are unlikely to gain public approval.…”
Section: Novel Rabies Vaccine Candidatesmentioning
confidence: 99%